NON-PERFORMING LOANS: ANALYSIS AND REGULATION - lobozynska, sophia (Acta Universitatis Lodziensis. Folia Oeconomica, 2014)
The analysis of the level of non-performing loans and the volumes of forming the insurance reserves for them with a time lag of 6 years (2004–2009) in developing countries (China, Poland, Russia, Ukraine) was made. The estimation of efficiency of regulatory processes to combat non-performing loans of the banking sector which were applied by these countries was provided. The correlation-regression model of establishing cause-effect relationship between effective index – the share of non-performing loans in the loan portfolio of the banking system and the independent variables was developed and tested. The recommendations on the mechanisms to minimize the amount of non-performing loans were given.